Beginning university : thinking, researching and writing for success - Wallace, Andrew, 1945-; Schirato, Tony.; Bright, Phillippa (St Leonards, N.S.W : Allen and Unwin, 1999)
Background; The basics; Learning strategies; Assignments; and Beyond university.
Keywords: Education; Australia; Study; Universities and colleges; Study skills -- Australia; Universities and colleges -- Australia